Allopurinol for mania: a randomized trial of allopurinol versus placebo as add‐on treatment to mood stabilizers and/or antipsychotic agents in manic patients with bipolar disorder. (8th April 2014) - Weiser, Mark; Burshtein, Shimon; Gershon, Ari A; Marian, Gabriela; Vlad, Nicolae; Grecu, Iosif G; Tocari, Elena; Tiugan, Alexandru; Hotineanu, Mihail; Davis, John M
<x xml:space="preserve">Abstract</x> Objective An emerging body of evidence supports a role for dysfunctional purinergic neurotransmission in mood disorders. Adenosine agonists have been shown to have properties similar to those of dopamine antagonists; there is a well‐characterized interaction between adenosine and dopamine receptors in the ventral striatum, and increasing adenosinergic transmission has been demonstrated to reduce the affinity of dopamine agonists for dopamine receptors. Allopurinol increases adenosine levels in the brain, and hence is hypothesized to reduce the symptoms of mania. Two randomized, placebo‐controlled trials administering add‐on allopurinol to manic patients showed significantly greater improvements in Young Mania Rating Scale (YMRS) scores for drug compared to placebo, while a more recent, relatively small, add‐on study showed negative results. Based on these data, our objective was to examine the efficacy of allopurinol as add‐on treatment to mood stabilizers and/or antipsychotic agents in manic patients with bipolar disorder. Methods We performed a large, well‐powered, multicenter, six‐week, randomized, placebo‐controlled trial of allopurinol added to mood stabilizers and/or antipsychotic agents in 180 patients with bipolar disorder in an acute manic episode. Results Both groups showed improvement on the YMRS (effect size of 1.5 for placebo and 1.6 for allopurinol), with no difference observed between groups on YMRS scores (t = 0.28, p = 0.78). There was no difference in the proportion of patients who responded to treatment (defined as showing at least 50% improvement in YMRS score) between the two groups (p = 0.92), or in dropout rates (p = 0.84). Limitations None of our patients received lithium. However, the side effects of lithium and its narrow therapeutic index made the use of lithium less common and, therefore, our study results reflect common current clinical practice. In the present study, we used a variety of antipsychotic and/or mood stabilizing treatments, to which we added allopurinol; one might hypothesize that add‐on allopurinol has a different effect in combination with different antipsychotic agents or mood stabilizers. Conclusions The findings of this large, well‐powered study do not support add‐on allopurinol as a treatment for acute mania. This study did not test the efficacy of allopurinol as monotherapy.